From Coast to Highlands: A Cross-Regional SWOT/SOAR Analysis of 14 Indonesian Tourism Villages - Yulius, Kevin Gustian; Timba, Yosep Dudedes (Institut Pariwisata Trisakti, 2025)
This study examines strategic capacities and aspirations of 14 Indonesian tourism villages through a cross-regional SWOT and SOAR analysis. Using a qualitative multiple-case study design, semi-structured interviews was conducted with one Pokdarwis (Tourism Awareness Group) representative per village and reviewed secondary documents, coding data manually in Excel. Thematic analysis identified three core strengths rich natural attractions, distinctive cultural heritage, and active community involvement and three primary weaknesses underdeveloped infrastructure, limited strategic capacity, and low digital promotion. Key opportunities emerged around digital marketing, niche tourism product development, and multi-stakeholder collaboration, while environmental risks and fragmented governance surfaced as major threats. Informants’ aspirations centered on becoming models of eco-cultural tourism, empowering youth, and integrating tradition with modern strategies. Early results include increased homestay revenues, growth of MSMEs, and the revival of cultural events, demonstrating that asset-based planning coupled with targeted capacity building can yield sustainable outcomes. The findings underscore the value of combining diagnostic (SWOT) and forward-looking (SOAR) frameworks to guide community-based tourism development and offer practical insights for policymakers and practitioners aiming to foster inclusive growth, cultural preservation, and ecological resilience. Keywords: community-based tourism, tourism village, SOAR framework, sustainable development, SWOT analysis